Enhancing High School Teachers’ Online Teaching Capacity Through Contextualized Training in Southern Thailand - M Nurul Ikhsan Saleh; Mir'atun Nur Arifah (Altifani Journal: International Journal of Community Engagement, 2025)
Online teaching and learning have become commonplace in educational institutions since the outbreak of the COVID-19 pandemic. Even after the pandemic subsided, many institutions continued to adopt online or hybrid learning because of its flexibility, allowing education to take place from virtually anywhere. However, limited teacher skills in conducting online instruction can negatively affect the quality of the learning process and outcomes. This international community engagement initiative aimed to analyze the enhancement of teacher capacity through innovative online teaching training at the Sasnupatam School, Pattani, Thailand. The program was conducted in collaboration with the Department of Islamic Studies, Faculty of Islamic Studies, Universitas Islam Indonesia. The methods employed in this initiative included remote observations and interviews with key stakeholders at the Sasnupatam School. The program’s main concept focused on providing high school teachers with online teaching techniques. Based on the results of the observations and interviews, the proposed solution was to conduct an online teaching training program for teachers. The training outcomes indicated that teachers improved their skills in utilizing educational applications, classroom management, and motivation-based teaching approaches. The three main topics covered in the training were motivation-based instructional design, selection of appropriate learning media, and active learning methods in online teaching contexts. The program was successfully implemented and contributed to teachers’ improved capacity in designing engaging online lessons through motivation-based approaches, effective media selection, and active learning practices.